2019
DOI: 10.1007/s00198-018-04826-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of osteonecrosis among older adults in Sweden

Abstract: Summary This study estimated the incidence of osteonecrosis in a Swedish, nationwide cohort of older adults. Osteonecrosis was approximately 10 times more common than in previous studies. The strongest risk factors were dialysis, hip fracture, osteomyelitis, and organ transplantation, but only hip fractures could have contributed substantially to the disease burden. Introduction The aim of this study was to estimate the incidence of osteonecrosis in a Swedish, nationwid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 38 publications
0
25
0
3
Order By: Relevance
“…Finally, given the observational study design, the associations found are most likely influenced by different forms of bias and confounding. Thus, although a recent study in a similar cohort suggested that only hip fracture contribute substantially to the risk of osteonecrosis, there may be unknown confounders that could influence the associations found in the present study. With respect to previous fractures as a risk factor, it should also be noted that from registers it is not possible to determine if a previous fracture occurred at the same side as later osteonecrosis.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Finally, given the observational study design, the associations found are most likely influenced by different forms of bias and confounding. Thus, although a recent study in a similar cohort suggested that only hip fracture contribute substantially to the risk of osteonecrosis, there may be unknown confounders that could influence the associations found in the present study. With respect to previous fractures as a risk factor, it should also be noted that from registers it is not possible to determine if a previous fracture occurred at the same side as later osteonecrosis.…”
Section: Discussionmentioning
confidence: 54%
“…This possibility would produce a false association between BSD and osteonecrosis. However, it should be noted that this was not the case in a recent validation study, where 30 cases of osteonecrosis were validated for accuracy . Finally, given the observational study design, the associations found are most likely influenced by different forms of bias and confounding.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Osteoarthritis is currently the fourth leading cause of disability in women and the eighth in men. Among the most common causes of osteoarthritis of the hip due to sterile femoral head necrosis are: chronic dialysis, femoral neck fracture, hip in ammation, immunosuppression in organ transplantation [1].Sterile osteonecrosis of the femoral head, as the second cause of osteoarthritis in young patients, is almost 10 times more common in the male population than earlier research results might suggest.This disease at such a young age is the reason for giving up physical activity, absenteeism from work and often is found in patients undergoing treatment for a "different" disease [1,2].…”
Section: Introductionmentioning
confidence: 86%